Dual-frequency ultrasonic oxidation of cyanobacterial toxins (MC-LR and MC-RR) at drinking water resources: Assessment of analytical methods and ultrasonic reactor configuration - Zeynep Eren (Ultrasonics Sonochemistry)
Ultrasonic oxidation provides the degradation of a wide range of water pollutants to the final products defined as carbon dioxide, short-chain organic acids, and inorganic ions, typically less toxic and favorable to biodegradation. In this study, it was investigated the application of novel ultrasonic reactor that allows the several combinations of low (20 kHz and 40 kHz) and high frequency ultrasonic piezoceramic transducer (578 kHz, 862 kHz and 1142 kHz) to degrade two main cyanobacterial toxins, Microcystin-RR (MC-RR) and Microcystin-LR (MC-LR). A plate transducer operating at different frequencies (40 kHz or 578 kHz/862 kHz/1142 kHz) was combined with a probe (20 kHz) as well as two plate transducers 40 kHz and 578 kHz/862 kHz/1142 kHz were combined to provide dual frequency ultrasonic reactor (DFUR). In order to carry out the study successfully, it is necessary to detect and monitor microcystins (MCs) using sensitive, robust, selective and reliable analytical methods. In this work, it was simultaneously identified and quantified with liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) without any phase extraction for sample preparation. Ultrasonic oxidation of MC-RR and MC-LR by DFUR exhibited more suitable degradation rate with second order than a very small difference from first-order reaction. A comprehensive standardization method for ultrasonic sources were considered based on calorimetry, chemical dosimetry, cavitational yield, energy efficiency as well.